Friends and Neighbours: Electoral Geography of 2020 Local Election in Metro City, Lampung, Indonesia - Arizka Warganegara; Ari Darmastuti; Hertanto Hertanto; R Sigit Krisbintoro; Muhammad Febriansyah; Wahyu Tyas Pramono (Forum Geografi, 2023)
This article discusses local political dynamics in Indonesia, notably in the city of Metro. There are several factors why a particular candidate is more politically electable than others, including ethno-religious factors and money. Moreover, a traditional factor that needs to be considered in the study of electoral geography is the influence of the spatial effect upon voting behaviour. In the election, demographics and geography are two important factors in voting behaviour. The local election resulted in a competitive and dynamic political contest among the local elite in Metro. The result of the 2020 local election was particularly interesting because the independent candidate won and defeated the party-based candidate. This is a mixed methods approach combining the data from interviews and a qualitative survey. This research aims to analyse the spatial factor in Metro’s local election, looking at why a certain candidate won in a particular area and how the geographical factor influenced voting behaviour. Secondly, the result of the qualitative survey supported the finding that voters still consider ethno-religious factor. The finding obtained by this research reveals two significant narratives, specifically the crucial factor of ethno-religious sentiment on voting preference and the spatial factor related to residency in securing a victory for the candidate in the local election. Essentially, research concludes that the spatial factor is of importance in the context of Metro’s local election and supports Woolstencroft's (1980) classical concept of electoral geography comprising “friends and neighbours”.